Towards A Classroom Condition Index (CCI) Assessment Scheme: Assessment Categories And Their Performance Indicator - Norsafiah Norazman; Adi Irfan Che-Ani; Afifuddin Husairi Mat Jusoh Hussain; Wan Norisma Wan Ismail (Emerald Publishing Limited, 2024)
Indexed by ERA